FAMILY EXPERIENCE IN PARENTING STUNTING TODDLERS - Simanjuntak, Daddy Deo Gilbert Pamungkas; Rahmawati, Nadia; Mita, Mita (Jurnal Keperawatan dan Kesehatan, 2025)
Background: Stunting cases occur throughout the world, with many toddlers in various countries experiencing stunting and chronic malnutrition. Data from the UNICEF in 2020 shows that 22% of all children in the world, or around 149.2 million children suffer from stunting. The results of the Indonesian Nutritional Status Study (SSGI), the prevalence of stunted toddlers in Indonesia was 24.4% in 2021. In 2021, West Kalimantan was in 7th place nationally with a stunted toddler prevalence of 29.8%. Sambas Regency is one of the districts with the largest stunting rate in West Kalimantan with 5,500 stunted children under five. Aim of research: To find out the families' experiences in caring for stunting toddlers in Sambas Regency. Methods: Qualitative research with phenomenological study approach. The participants involved in this study as many as 5 people were selected with purposive sampling techniques. Data collection using in-depth interview method. Scientific finding results: The results of this research found 7 themes, namely sources of information, feelings, child feeding challenges, parenting support, obstacles to children's eating, selection of children's meal menu and sources of water for consumption. Conclusion: Children's eating problems were one of the most common factors causing stunting in this study. Parenting style is an important factor in a child's growth and development. It is important to apply good parenting patterns to children so that children get the nutrition they need to grow and develop well and avoid stunting.